Interaction of carbon monoxide-releasing ruthenium carbonyl CORM-3 with plasma fibronectin. (August 2018) - Aki, Toshihiko; Unuma, Kana; Noritake, Kanako; Kurahashi, Hatsumi; Funakoshi, Takeshi; Uemura, Koichi
Abstract: Inhaled carbon monoxide (CO) gas is highly toxic, but the human body produces low levels of CO for vasoregulation and other purposes. Given the established protective roles of low concentrations of CO gas against a panel of pathological insults, CO-releasing molecules (CORMs) have been developed and examined in disease models both in vitro and in vivo . Among CORMs, CORM-3 [Ru(CO)3 Cl(glycinate)], a ruthenium carbonyl compound, has been extensively studied since it is water-soluble and is suitable for in vivo application. As one of the most prominent features of CO gas is its anti-fibrotic effect, we examined the effects of CORM-3 on mouse embryonic fibroblasts (MEFs). The application of 1 mM CORM-3 to MEFs resulted in the decreased syntheses of collagens I and III within 24 h, confirming an anti-fibrotic effect. To our surprise, CORM-3 caused a rapid (within 1 h) dissociation of cell-associated plasma fibronectin (FN) from the cells, which is associated with formation of a reduction-resistant oligomer of plasma FN. This aberrant oligomerization of plasma FN was reproduced using purified FN in vitro . Furthermore, we showed that RuCl3, but not another water-soluble CORM, CORM-A1 [Na2 H3 BCO2 ], also oligomerized plasma FN in vitro . FN depletion from the serum substantially ameliorates cell death by prolonged (72 h) exposure to CORM-3, suggesting a detrimental role of FN oligomerization on cell death. Taken together, we reveal for the first time that FN is a CORM-3-interactive plasma protein, and that the CORM-3-FN interaction is involved in the death of fibroblasts. Highlights: CORM-3 causes oligomerization of fibronectin. Rutehnium within CORM-3 is responsible for this reaction. Oligomerized fibronectin is detrimental to cell survival.